1993
DOI: 10.1152/ajpgi.1993.264.1.g36
|View full text |Cite
|
Sign up to set email alerts
|

Na(+)-independent multispecific anion transporter mediates active transport of pravastatin into rat liver

Abstract: To examine whether the relatively selective inhibition of hepatic cholesterol synthesis by the hydrophilic 3-hydroxyl-3-methylglutaryl-coenzyme A (HMG-CoA) reductase inhibitor pravastatin in vivo may be due to the existence of a specific uptake mechanism in the liver, the uptake by isolated rat hepatocytes was investigated. The uptake was composed of a saturable component [Michaelis constant (Km) 29 microM, maximal uptake rate 546 pmol.min-1.mg-1] and nonspecific diffusion (nonspecific uptake clearance 1.6 mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
86
2
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(96 citation statements)
references
References 0 publications
7
86
2
1
Order By: Relevance
“…Nowadays, 3 kinds of organic anion transporters have been demonstrated in human liver cells [7]; among them, organic anion transporter type-2 (OATP-2) has been noted to be involved in the uptake of many drugs into liver cells. Similar transporters to this OATP-2 were confirmed in the rat liver, OATP-1/4 (3,17). It has been reported that endogenous reduced folate [8], PV [9,18] and methotrexate [11] are the substrate of these transporters.…”
Section: Discussionsupporting
confidence: 69%
“…Nowadays, 3 kinds of organic anion transporters have been demonstrated in human liver cells [7]; among them, organic anion transporter type-2 (OATP-2) has been noted to be involved in the uptake of many drugs into liver cells. Similar transporters to this OATP-2 were confirmed in the rat liver, OATP-1/4 (3,17). It has been reported that endogenous reduced folate [8], PV [9,18] and methotrexate [11] are the substrate of these transporters.…”
Section: Discussionsupporting
confidence: 69%
“…Pravastatin is a hydrophilic molecule and is selectively taken up by hepatocytes via Na -independent multispecific anion transporters and energy-dependent transporters 22) , thereby having a direct effect on the liver. It has also been reported that pravastatin, but not other hydrophobic statins, can exert beneficial effects on some phenotypes of hepatocytes 23,24) .…”
Section: Discussionmentioning
confidence: 99%
“…Pravastatin is the most hydrophilic statin among the statins now in use and inhibits cholesterol biosynthesis selectively in hepatocytes 49) , while simvastatin, a hydrophobic statin, inhibits HMG-CoA reductase in all organs [46][47][48][49] . It has been reported that the relatively selective inhibition of hepatic cholesterol synthesis by hydrophilic pravastatin in vivo might be due to the existence of a specific uptake mechanism mediated by the Na( )-independent multispecific anion transporter system in the liver 50,51) .…”
Section: Discussionmentioning
confidence: 99%